Math, asked by shreya3212, 11 months ago

please help me and wrong answer will be reported so please give the right answer​

Attachments:

Answers

Answered by IamNehaRoy
4

Hope this helps you ;)

(k - 2)x + 4y = 10

given \: x = 2 \: and \: y = 1

On substituting x and y,

(k - 2) \times 2 + 4(1) = 10

(k - 2) \times 2 = 10 - 4

(k - 2) =   \frac{6}{2}

k =  3+ 2

k = 5

Answered by Anonymous
0

Answer:

Hope this helps you ;)

(k - 2)x + 4y = 10(k−2)x+4y=10

given \: x = 2 \: and \: y = 1givenx=2andy=1

On substituting x and y,

(k - 2) \times 2 + 4(1) = 10(k−2)×2+4(1)=10

(k - 2) \times 2 = 10 - 4(k−2)×2=10−4

(k - 2) = \frac{6}{2}(k−2)=

2

6

k = 3+ 2k=3+2

k = 5k=5

Similar questions